Literature Review: Utilization of Technology and Computerization in Smart Homes - Arifin, Ismail; Dwi Cahya, Deni (SMART : Jurnal Teknologi Informasi dan Komputer, 2022)
The development of information technology and the Internet of Things (IoT) has brought significant changes to smart home systems. This article presents a literature review of five studies from accredited national and international journals that discuss the application of technology to smart homes between 2017 and 2022. The main focus includes system architecture, inter-device communication, automation, security, and energy efficiency. Based on the review results, the application of IoT technology and artificial intelligence (AI) plays a significant role in realizing smart homes that are efficient and adaptable to occupant needs. The main challenges lie in data security, system interoperability, and implementation costs. This study is expected to serve as a reference for researchers and practitioners in developing smart home innovations that are safer, energy-efficient, and user-friendly.